2011
DOI: 10.3926/jiem.2011.v4n3.p418-435
|View full text |Cite
|
Sign up to set email alerts
|

A methodological approach for designing and sequencing product families in Reconfigurable Disassembly Systems

Abstract: Abstract:Purpose: A Reconfigurable Disassembly System (RDS) represents a new paradigm of automated disassembly system that uses reconfigurable manufacturing technology for fast adaptation to changes in the quantity and mix of products to disassemble. This paper deals with a methodology for designing and sequencing product families in RDS.Design/methodology/approach: The methodology is developed in a two-phase approach, where products are first grouped into families and then families are sequenced through the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…As pointed Since disassembly is an important part of remanufacturing systems for reuse and recycling purposes, automation and digitalization have a growing number of applications in the area of WEEE. For this reason, reconfigurability of disassembly systems represents an important paradigm of automated disassembly system that uses reconfigurable manufacturing technology for fast adaptation to changes in the quantity and mix of products to disassemble [64]. However, there are still many barriers in reverse production process adoption due to the complexity of the most of manufacturing systems and to the high number of product and components to be treated.…”
Section: Test Of the Disassembly Processmentioning
confidence: 99%
“…As pointed Since disassembly is an important part of remanufacturing systems for reuse and recycling purposes, automation and digitalization have a growing number of applications in the area of WEEE. For this reason, reconfigurability of disassembly systems represents an important paradigm of automated disassembly system that uses reconfigurable manufacturing technology for fast adaptation to changes in the quantity and mix of products to disassemble [64]. However, there are still many barriers in reverse production process adoption due to the complexity of the most of manufacturing systems and to the high number of product and components to be treated.…”
Section: Test Of the Disassembly Processmentioning
confidence: 99%
“…Grouping results are used to find the best sequence of product variants. In this algorithm, products with higher coefficient of similarity are grouped together (Vakharia and Wemmerlöv 1995;Galan et al 2007aGalan et al , 2007bEguia et al 2011Eguia et al , 2013. A submatrix consisting of grouped and ungrouped products is then constructed.…”
Section: Alc Algorithmmentioning
confidence: 99%
“…That is why recycling is important in green manufacturing. The importance of industrial recycling and remanufacturing is growing due to increas-ing environmental and economic pressures (Eguia, et al, 2011) Only 22.22% of the respondents reported a very significant decrease in the total expenses due to reducing packaging materials used; 33.33% of the respondents reported a significant decrease in total expenses, and the same percentage of respondents reported that the green initiative did not affect the financial performance of the firm. The respondents who reported that there was only a significant decrease in total expenses was only 11.11%.…”
Section: Impact Of Green Initiatives On the Financial Performance Of The Small And Medium Manufacturing Enterprisesmentioning
confidence: 99%